ভাষা আন্দোলন : টেকনাফ থেকে তেঁতুলিয়া - রফিক, আহমদ (ঢাকা : প্রথমা প্রকাশন, 2019)
History of Bengali language movement from Bangladesh.
গ্রন্থপঞ্জিগত নির্দেশিকা (পৃষ্ঠা ১৮৮-১৮৯) ও নির্ঘণ্ট অন্তর্ভুক্ত।
Donated By Akbar Ali Khan
In Bengali.
Keywords: Bengali language movement; Language policy -- Bangladesh -- History; Bengali language -- Political aspects -- Bangladesh; Bengali language -- Usage; Bangladesh -- Politics and government -- 1971-